Stratigraphy and Tectonics of the Sengkang Basin, South Sulawesi - Suyono, Suyono; Kusnama, Kusnama (Geological Agency, 2010)
DOI:Â 10.17014/ijog.v5i1.89Sulawesi was formed during the Oligocene - Miocene collision between the Eurasian Plate and micro-continental fragments detached from the Indian-Australian Plate. The Sengkang Basin situated on the South Sulawesi Province, was formed by a major north northwest - south southeast trending fault system of the Walanae Fault Zone, which was followed by the formation of Late Neogene foreland basin and syn-orogenic deposition. The fault system separated the eastern and western parts of South Sulawesi and influenced the deposition during the Late Miocene to Quaternary. The lower part of the deposition unit consists of small carbonate reefs of the Tacipi Member occupying the East Sengkang Basin, where this shallow marine facies is intercalated within or overlies marine claystones representing the base of the Walanae Formation. The middle sequence is interpreted as a delta foreset consisting of the Samaoling and Beru Members. During the deposition of these two members, the northern part of the Sengkang Basin gradually changed from a tidal and deltaic to fluvial environments. Furthermore, the upper sequence of this sedimentary unit is dominated by fluvial deposits.